ANALYSIS OF SOME ECONOMICALLY VALUABLE TRAITS OF FORAGE CROPS - Allashov B.D; Ahmedov T.P; Zulfiqorov M.X; Erdanova G. M; Erimbetova J. B; Parmanova D.M (Utilitas Mathematica, 2025)
In the successful development of livestock industries, the feed base is of great importance. In order to improve the productivity of livestock, it is necessary to have a solid feed base. The main part of feed for livestock is grown on agricultural land. For this reason, effective use of agricultural land and achieving the highest possible yield from nutritious crops are urgent tasks. Currently, more than half of the irrigated lands in Uzbekistan are saline to varying degrees. In addition, problems such as water shortage and abnormal heat in the summer are increasing year by year in the republic. Naturally, in water-scarce and saline lands, the possibility of obtaining high yields from agricultural crops, including nutritious crops, decreases. For this purpose, it is necessary to plant nutritious crop types and varieties suitable for the soil and climate conditions of such regions. Among the food crops, sorghum and African millet crops are resistant to water shortage, salinity and heat. The Scientific-Research Institute of Plant Genetic Resources has a National Genebank, which stores varieties and samples of all types of agricultural crops. We took 10 samples from the sorghum crop and 10 samples from the African millet crop to be included in our experiments. Research work was carried out on collection samples of sorghum and African millet crops obtained from the National Genebank and studied for some valuable economic traits. This paper presents the results of studies on some valuable economic traits in nutritive crops such as sorghum and African sorghum.